Middle Ages or Renaissance? Rapacka on Marulić - Bogdan, Tomislav (Poznańskie Studia Slawistyczne, 2024)
The famous Polish Slavist Joanna Rapacka published three studies on Marko Marulić. After they came out as separate publications, she collected them under the title Fragmenti o Maruliću (Fragments on Marulić). Rapacka refers to Marko Marulić extensively in several other works, such as the articles in her Leksykon tradycji chorwackich (Lexicon of Croatian Traditions) or in synthesizing studies on the formation of the modern Croatian nation and on regionalism in pre-modern Croatian literary culture. Her views of Marulić are worth citing and examining for two reasons: because they can still be relevant for the understanding of Marulić’s literary works and because in present-day Croatian studies they have not had the appreciation they deserve. Rapacka groups Marulić, and particularly the vernacular part of his opus, closely together with the poetics of the European literary Middle Ages, while Croatian literary historiography has in the last few decades exerted great efforts to “demedievalize” Marulić. When one reads the writings of Rapacka carefully, it becomes clear that she sees him as the first great author of medieval Croatian literature.